Thermoregulatory and Metabolic Demands of Naval Special Warfare Divers During a 6-h Cold-Water Training Dive - Chapin, Andrea C.; Arrington, Laura J.; Bernards, Jake R.; Kelly, Karen R. (Frontiers in Physiology, 2021)
Introduction: Extreme environmental conditions induce changes in metabolic rate and substrate use due to thermoregulation. Cold-water full-body submersion for extended periods of time is inevitable for training and missions carried out by Naval Special Warfare divers. Anthropometric, physiologic, and metabolic data have been reported from partial immersion in cold water in non-thermally protected men; data is limited in thermally protected divers in extremely cold water. Thermoregulatory and metabolic demands during prolonged cold-water submersion in Naval Special Warfare divers are unknown. Objective: Assess thermoregulatory and metabolic demands of Naval Special Warfare divers surrounding prolonged cold-water submersion. Materials and Methods: Sixteen active-duty U.S. Navy Sea Air and Land (SEAL) operators tasked with cold-water dive training participated. Divers donned standard military special operations diving equipment and fully submerged to a depth of ∼ 6 m in a pool chilled to 5°C for a 6-h live training exercise. Metabolic measurements were obtained via indirect calorimetry for 10-min pre-dive and 5-min post dive. Heart rate, skin temperature, and core temperature were measured throughout the dive. Results: Core temperature was maintained at the end of the 6-h dive, 36.8 ± 0.4°C and was not correlated to body composition (body fat percentage, lean body mass) or metabolic rate. SEALs were not at risk for non-freezing cold injuries as mean skin temperature was 28.5 ± 1.6°C at end of the 6-h dive. Metabolic rate (kcal/min) was different pre- to post-dive, increasing from 1.9 ± 0.2 kcal/min to 2.8 ± 0.2 kcal/min, p < 0.001, 95% CI [0.8, 1.3], Cohen’s d effect size 2.3. Post-dive substrate utilization was 57.5% carbohydrate, 0.40 ± 0.16 g/min, and 42.5% fat, 0.13 ± 0.04 g/min. Conclusion: Wetsuits supported effective thermoprotection in conjunction with increase in thermogenesis during a 6-h full submersion dive in 5°C. Core temperature was preserved with an expected decrease in skin temperature. Sustained cold-water diving resulted in a 53% increase in energy expenditure. While all participants increased thermogenesis, there was high inter-individual variability in metabolic rate and substrate utilization. Variability in metabolic demands may be attributable to individual physiologic adjustments due to prior cold exposure patterns of divers. This suggests that variations in metabolic adjustments and habituation to the cold were likely. More work is needed to fully understand inter-individual metabolic variability to prolonged cold-water submersion.